Intensified sensitivity and adaptability of zooplankton Bosminidae in subtropical shallow freshwater lakes with increasing trophic level - Cheng, Longjuan; Gao, Xinyuan; Wang, Guangwei; Ding, Zhou; Xue, Bin; Zhang, Can; Liu, Jinliang; Jiang, Qingfeng (Frontiers in Ecology and Evolution, 2023)
The deterioration of lake environments is obvious all over the world, especially increasing lake eutrophication, which has seriously affected the balance and stability of the internal ecosystem of lakes. In this study, modern water and sediment samples were collected from three subtropical freshwater lakes with significant differences in nutrient levels to analyze the concentration of zooplankton Cladocera Bosminidae and its relationship with lake ecological changes. Results show that the deterioration of the lake water environment caused by increasing eutrophication limits the survival of most zooplankton. However, the Bosminidae shows a positive adaptability to eutrophication and high sensitivity to the changes in the lake environment. In addition, the lake eutrophication process caused by the intensification of human activities enhances the survival advantage of Bosminidae with more food sources, which is more conducive to its rapid reproduction.